TAHAP ANALISIS UNTUK PENGEMBANGAN “ASETARO” KOMIK PENDIDIKAN KESEHATAN UNTUK ANAK TENTANG BAHAYA MEROKOK - Trixie Salawati; Nuke Devi Indrawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Smoking is harmful especially for children. Children must be protected from the effect of tobacco use. Comic story book is one of the children’s favorite media. Comic can serve health education purpose. The purpose of this study was to develop “Asetaro”, a Comic Story Book for primary school aged children, to help children learn about the effect of tobacco use for health. This study based on the steps of the media development model by Sadiman. The first step was analyze the characteristic and the need of the target group through FGD, interviews and literature review. Results of analysis studies showed that most students liked science fiction comics. Analysis study also revealed that the students still need information about the harm of cigarettes, why smoking can cause addiction and disease, as well as the impact of smoking on active and passive smokers. Analysis study also found that some students still believe that smoking is an adult’s behavior. Children are not allowed to smoke because the body is still weak. Based on the results of analysis studies was then to design and develop a draft of comic story book.Keywords: Analysis, Comic story book, Health Education, The effect of tobacco use for health